Developing a Wearable Sensor for Continuous Tissue Oxygenation Monitoring: A Proof of Concept Study - Kwasnicki, Richard M.; Chen, Ching-Mei; Noakes, Alex J.; Hettiaratchy, Shehan; Yang, Guang-Zhong; Darzi, Ara (Journal of Reconstructive Microsurgery Open, 2021)
Objective Technologies facilitating continuous free tissue flap monitoring such as near infrared spectroscopy (NIRS) have been shown to improve flap salvage rates. However, the size and associated costs of such technology create a barrier to wider implementation. The aim of this study was to develop and validate a wearable sensor for continuous tissue oxygenation monitoring.Materials and Methods A forearm ischemia model was designed by using a brachial pressure cuff inflation protocol. Twenty healthy subjects were recruited. The forearm tissue oxygenation of each subject was monitored throughout the pressure cuff protocol by using a new optical sensor (Imperial College London), and a gold standard tissue spectrometry system (O2C, Medizintecknik, LEA, Germany). Data were processed to allow quantitative deoxygenation episode comparisons between inflations and sensor modalities.Results The correlation between O2C and optical sensor oxygenation measurements was moderate (average R = 0.672, p < 0.001). Incremental increases in cuff inflation duration resulted in a linear increase in deoxygenation values with both O2C and optical sensors, with significant differences recorded on consecutive inflations (wall shear rate, p < 0.005). The presence or absence of pulsatile blood flow was correctly determined throughout by both sensor modalities.Conclusion This study demonstrates the ability of a small optical sensor to detect and quantify tissue oxygenation changes and assess the presence of pulsatile blood flow. Low power, miniaturized electronics make the device capable of deployment in a wearable form which may break down the barriers for implementation in postoperative flap monitoring.
Keywords: plastic surgery; free flap monitoring; technology; tissue oxygenation